Evaluation of Standard Procedures Operational in Tabanan District General Hospital: Usage of Special Control Antimicrobials (Restrictions) - Noviyani, Rini; Putri, A. A. Sagung Indah Candra; Putri, Ni Wayan Prasanthi Swarna; Ekayanti, Ni Kd Rintan Listiani; Widatama, Agata (Jurnal Ilmiah Farmasi, 2024)
Background: The healthcare sector, specifically hospitals, is vulnerable to antimicrobial resistance due to diverse services and patient populations, alongside continuous intensive antimicrobial use. This resistance presents a significant national and global health threat. Therefore, implementing an antimicrobial stewardship program is crucial for reducing resistance development and spread in hospitals. Pharmacists, as healthcare professionals, have an essential role in upholding stewardship through pharmaceutical services in line with Standard Operating Procedure (SOP).Objective: This study aimed to evaluate Restricted Antimicrobial Standard Operating Procedure (SOP-A) at Tabanan Regional General Hospital (RSUD Tabanan) to enhance the quality of pharmaceutical services.Method: A qualitative method was used in SOP evaluation, comparing data from interviews with the Head of Pharmacy Installation at RSUD Tabanan and observations of implementation. The data were then contrasted with recent literature and regulations to identify discrepancies necessitating improvements. Moreover, data were analyzed using the descriptive method and presented in narrative, figure, and table formats.Results: The results showed that based on interviews and observations of SOP-A implementation, several revisions were needed. These revisions include adding restricted antimicrobials from the reserve categories (cefepime, cefpirome, and carbapenems), establishing a protocol for eligible patients without waiting for culture results, outlining a process for obtaining approval from the Head of the Antimicrobial Resistance Control Program (PPRA) and Hospital Director, as well as incorporating antimicrobial usage history into the restricted antibiotic use application form.Conclusion: SOP-A at RSUD Tabanan requires four key additions, namely a list of reserve category antimicrobials, a protocol for administering restricted antimicrobials to eligible patients without waiting for culture results, a process for obtaining approval from the Head of the PPRA and Hospital Director, as well as inclusion of antimicrobial usage history in the restricted antibiotic use application form.